Immunohistochemical evaluation of Ki-67 and PCNA in canine mammary neoplasias: Correlation with prognostic factors and clinical outcome - Zuccari, Debora A. P. C.; Pavam, Marcilia V.; Terzian, Ana Carolina B. [UNESP]; Pereira, Rodrigo S.; Ruiz, Camila M.; Andrade, Joanna Coelho (Revista Pesquisa Veterinaria Brasileira, 2008)
E-cadherin is a cell-cell adhesion molecule and low e-cadherin expression is related to invasiveness and may indicate a bad prognosis in mammary neoplasms. The expression of cell proliferation markers PCNA and especially Ki-67, has also proved to have a strong prognostic value in this tumor class. The expression of these markers was related to the clinical-pathological characteristics of 73 surgically removed mammary tumors in female dogs by immunohistochemistry. There was no statistical correlation between these markers and death by neoplasm, survival time and disease-free interval. However, the loss of e-cadherin expression and marked Ki-67 expression (p=0.016) were considered statistically significant for the diagnosis (p=0.032). When evaluated as independent factors, there was evidence of the relationship between the loss of e-cadherin expression and high PCNA expression with changes in the body status (divided into obese, normal and cachectic) of female dogs (p=0.030); there was also evidence of the relationship between pseudopregnancy and e-cadherin alone (p=0.021) and for ulceration and PCNA alone (p=0.035). The significant correlation between the markers expression and these well known prognostic factors used individually or in combination suggests their prognostic value in canine mammary tumors.
Avaliação imuno-histoquímica da e-caderina, Ki-67 e PCNA nas neoplasias mamárias caninas: correlação dos fatores prognósticos com a evolução clínica
Keywords: Canine; Dell proliferation marker; E-cadherin; Immunohistochemistry; Mammary neoplasm